Change in rat meibomian gland structure with external pressure on the eyelid. Issue 5 (October 2022) - Eom, Youngsub; Kang, Boram; Li, Xiangzhe; Hwang, Ho Sik; Lee, Hyung Keun; Kim, Hyo Myung; Song, Jong Suk
Abstract: Purpose: This study investigated structural changes in rat meibomian glands following repeated and sustained application of external pressure on the eyelids using a magnet and then subsequent removal of the external pressure. Methods: Twenty-eight Sprague-Dawley rats were used. The upper eyelid was externally compressed using a pair of magnets. One magnet was placed inside the upper eyelid, another was placed outside the eyelid, and varying periods of pressure were investigated. Untreated eyes were used as controls. Meibography was performed, and the transverse eyelid tissue sections were stained with hematoxylin and eosin and anti-cytokeratin 5 antibody at one hour, two and four weeks after removing the magnets. Results: Meibography showed increased meibomian gland loss (30.0 ± 5.0%), and tissue sections showed decreased area of secretory acini (0.04 ± 0.08 mm 2 ) at one hour after applying external pressure using magnets versus in the control eyes (5.0 ± 5.0% and 0.08 ± 0.08 mm 2, respectively). On the other hand, there was no meibomian gland loss or reduction of the area of secretory acini at two and four weeks after removing the magnets in comparison with the control eyes. Conclusions: Repeated and sustained application of external pressure on the eyelid could induce meibomian gland loss; however, this meibomian gland loss can be restored when the external pressure is removed. Therefore, the repeated application of external pressure on the eyelid is a safe treatment method for obstructive MGD.